Efektivitas dan Kontribusi Pajak Restoran Terhadap Pendapatan Asli Daerah - Tehusiarana, Dorris; Pelamonia, Julie Th.; Siahaya, Septina L. (Journal of Applied Accounting, 2025)
The purpose of this study was to determine the effectiveness of restaurant tax and its contribution to the Local Own Source Revenue of Central Maluku Regency. This type of research is quantitative descriptive research, which refers to the list of restaurant tax receipts and financial reports of Central Maluku Regency from 2019 to 2023. The data source in this study is secondary data. The data collection method uses the documentation method. The results of the analysis show that the average value of restaurant tax effectiveness is 74.41% so that it is included in the less effective category. While the results of the calculation of the average contribution value show that restaurant tax has no contribution to Local Own Source Revenue . Keywords: effectiveness, contribution, restaurant tax, local own source revenue